2016
DOI: 10.1371/journal.pone.0155929
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled Evolution between Senders and Receivers in the Neotropical Allobates femoralis Frog Complex

Abstract: During acoustic communication, an audible message is transmitted from a sender to a receiver, often producing changes in behavior. In a system where evolutionary changes of the sender do not result in a concomitant adjustment in the receiver, communication and species recognition could fail. However, the possibility of an evolutionary decoupling between sender and receiver has rarely been studied. Frog populations in the Allobates femoralis cryptic species complex are known for their extensive morphological, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Frogs also paid rather high attention (HBO) to more degraded signals in experiment 1 and responded indifferent to low and high SNR’s in experiment 2. This is in line with the previously identified rather broad temporal recognition space of A. femoralis (Göd et al 2007 ; Amézquita et al 2011 ; Vélez et al 2012 ; Betancourth-Cundar et al 2016 ). Hence, we conclude that signal detection and recognition were not jeopardized under the conditions of experiment 1 when using normalized, naturally degraded signals (cf.…”
Section: Discussionsupporting
confidence: 90%
“…Frogs also paid rather high attention (HBO) to more degraded signals in experiment 1 and responded indifferent to low and high SNR’s in experiment 2. This is in line with the previously identified rather broad temporal recognition space of A. femoralis (Göd et al 2007 ; Amézquita et al 2011 ; Vélez et al 2012 ; Betancourth-Cundar et al 2016 ). Hence, we conclude that signal detection and recognition were not jeopardized under the conditions of experiment 1 when using normalized, naturally degraded signals (cf.…”
Section: Discussionsupporting
confidence: 90%
“…Changes in the middle ear would take longer than those affecting vocalizations, originating the mismatch between the communication components observed in the central population; this also might explain the high spectral cross‐correlation of the tympanic sensitivity with the non‐local distress call. Faster evolution of signals than the reception/recognition system was proposed by Betancourth‐Cundar et al ( 2016 ) for the frog Allobates femoralis ; the authors found a decoupled evolution between signals (i.e., advertisement calls) and male–male recognition across different populations, suggesting that signal recognition evolves slower than call changes. In the same line, Penna et al ( 2015 ) proposed that the diversification process of the Alytes frogs may cause a secondary mismatch between call frequencies and the auditory sensitivity recorded in some species.…”
Section: Discussionmentioning
confidence: 86%
“…For example, two Brachycephalus frog species that lost their capability to hear their calls have retained the ability to vocalize (Goutte et al, 2017 ). Some factors that might explain this partial or total uncoupling include a short time for the selective pressures to act upon the paired adaptation of these components, the action of stochastic forces having stronger effects than the selective pressures that modulate the communication processes (e.g., Irwin et al, 2008 ; Kostarakos et al, 2009 ), and/or different selective pressures or evolutionary rates of the components (Ballentine, 2006 ; Betancourth‐Cundar et al, 2016 ; Zhao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our estimated detection probabilities demonstrate that multiple surveys of A. femoralis in the PMI are highly unlikely to result in false negatives (recorded absences when the species is actually present). We expected this result because A. femoralis is easily detectable even when it is scarce, especially because males respond reliably to playback calls ( Amézquita, Castellanos & Hödl, 2005 ; Amézquita et al, 2006 ; Betancourth-Cundar et al, 2016 ). Although the modules in the northeast (M1–M2 and M6–M9) show a more dispersed occupation of A. femoralis across plots, the average detectability did not markedly differ from modules of the southwest region (M10–M14) that have higher occurrences and relative abundances.…”
Section: Discussionmentioning
confidence: 93%
“…The ephemeral occurrence of suitable bodies of water also sometimes forces male A. femoralis to deposit tadpoles more than 180 m away from their territories ( Ringler et al, 2013 ), to which they reliably return ( Pašukonis et al, 2013 , 2014 ). Over the last two decades, A. femoralis has been used as a model species to address questions on diversification (e.g., Lougheed et al, 1999 ; Simões et al, 2008 ; Amézquita et al, 2009 ), sexual selection and parental care ( Ringler et al, 2015 , 2016 , 2017a ; Ursprung et al, 2011 ; Pašukonis et al, 2016 , 2017 ), movement ecology and spatial cognition ( Pašukonis et al, 2016 ; Beck et al, 2017 ), and communication ( Hödl, Amézquita & Narins, 2004 ; Amézquita, Castellanos & Hödl, 2005 ; Amézquita et al, 2006 ; Narins et al, 2005 ; Betancourth-Cundar et al, 2016 ; Ringler et al, 2017b ).…”
Section: Methodsmentioning
confidence: 99%